Cyclic Appearance and Disappearance of Aerosol Nucleation in the Boundary Layer of Drops of Volatile Liquid - Patrick Scheunemann; Mark Jermy; Paul Stephenson (Energies, 2023)
The cyclic appearance and disappearance of nucleation was observed in the boundary layer of drops of 1,3-propanediol, 1,2-propanediol, and glycerol, close to the boiling point and exposed to a cooler airflow. Although continuous nucleation has previously been widely observed, the cyclic nature of the phenomenon observed here is unusual. It was observed in experiments with free-falling drops and fixed drops in an upflow of air. To investigate this unexpected phenomenon further, the phenomenon was reproduced in two finite volume models. The first model used 1D potential flow solutions to approximate the airflow around the spherical windward face of the droplet. The second model used CFD to model the airflow. Both models used classical nucleation theory, the Stefan–Fuchs model of droplet growth by condensation, mass transfer by evaporation, diffusion, convection, and heat transfer by diffusion and convection. Despite several simplifications, the most important being the assumption that the drop has a uniform temperature, both models predict the frequency of nucleation to be better than the order of magnitude. These models also predict the experimentally observed power law dependence of nucleation frequency on air speed. It is proposed that the cyclic nature of the phenomenon is caused by the following process: the depletion of condensable vapour around the freshly nucleated aerosol due to condensation onto the aerosol results in reduced supersaturation, which stops further nucleation, and then the replenishment of this vapour by diffusion and convection from the parent drop, with nucleation of aerosol recommencing when the supersaturation has recovered sufficiently—then, the repetition of these steps in a cycle. It is proposed that the process depends mostly on the maximum saturation ratio in the boundary layer, which itself is determined by four key dimensionless numbers: the Lewis number, the Peclet number, the Reynolds number, and the ratio of the vapour pressure of the condensable compound at drop surface temperature to the vapour pressure of the same species at ambient temperature. A practical application of the phenomenon may be as a means of validation of thermo-fluid models, which include nucleation.